A Dual-Polarized Printed Antenna Based on a Tapered Slot SICL Balun for Airborne Radar Application. (14th March 2020) - Liu, Xiaochun; Wang, Li; Zhang, Mingxi; Liu, Shaobin; Du, Guiqiang
Abstract : The substrate-integrated coaxial line (SICL) is a potential transmission line due to its good characteristics of high efficiency, nondispersive, and single operational mode. A tapered slot SICL balun is proposed, which can realize the impedance transformation from the microstrip line to the coplanar strip line (CPS). At the same time, the proposed balun can transform the quasi-TEM mode of the microstrip line to the TEM mode of CPS. A printed dipole radiator is designed and is fed by the proposed SICL balun to achieve the impedance matching. The dual-polarized radiation mode is realized by employing two orthogonal printed dipoles. For each polarization radiator, the CPS is bended to avoided the occlusion of two polarization ports and realize the direct assembling of two orthogonal printed circuits. What is more, the assembling method is advantageous to improve the port isolation degree and decrease the cross polarization level. To improve the ratio of front to back (F/B) of the radiation pattern, a cylindrical metal cavity is adopted. According to the results of simulation and experiments, the VSWR of each port is lower than 2, the isolation degree between two polarization ports is higher than 20 dB, and the cross polarization level at the boresight is lower than −20 dB at the operational frequency. The patterns of two ports are almost symmetric, and high radiation efficiency is obtained. The experimental results of the principle prototype verify the design schemes of the balun and the dual-polarized antenna. The proposed dual-polarized antenna fed by the tapered slot SICL balun is suitable for the airborne radar application.